11.2k views
5 votes
Verify that the function u(x, y, z) = log x^2 + y^2 is a solution of the two dimensional Laplace equation u_xx + u_yy = 0 everywhere, except of course at the origin where f is not defined. Verify that the following functions solve the wave equation, u_tt = u_xx u(x, t) = cos(4x) cos(4t) u(x, t) = f(x - t) + f(x + 1), where f is any differentiable function of one variable.

1 Answer

3 votes

Answer:

The function
u(x,y,z)=log ( x^(2) +y^(2)) is indeed a solution of the two dimensional Laplace equation
u_(xx) +u_(yy) =0.

The wave equation
u_(tt) =u_(xx) is satisfied by the function
u(x,t)=cos(4x)cos(4t) but not by the function
u(x,t)=f(x-t)+f(x+1).

Explanation:

To verify that the function
u(x,y,z)=log ( x^(2) +y^(2)) is a solution of the 2D Laplace equation we calculate the second partial derivative with respect to x and then with respect to t.


u_(xx)=(2)/(ln(10))((x^(2) +y^(2))^(-1) -2x^(2) (x^(2) +y^(2))^(-2))


u_(yy)=(2)/(ln(10))((x^(2) +y^(2))^(-1) -2y^(2) (x^(2) +y^(2))^(-2))

then we introduce it in the equation
u_(xx) +u_(yy) =0

we get that
(2)/(ln(10)) ((2)/((x^(2)+y^(2)) ) - (2)/((x^(2)+y^(2) ) ) )=0

To see if the functions 1)
u(x,t)=cos(4x)cos(4t) and 2)
u(x,t)=f(x-t)+f(x+1) solve the wave equation we have to calculate the second partial derivative with respect to x and the with respect to t for each function. Then we see if they are equal.

1)
u_(xx)=-16 cos (4x) cos (4t)


u_(tt)=-16cos(4x)cos(4t)

we see for the above expressions that
u_(tt) =u_(xx)

2) with this function we will have to use the chain rule

If we call
s=x-t and
w=x+1 then we have that


u(x,t)=f(x-t)+f(x+1)=f(s)+f(w)

So
(\partial u)/(\partial x)=(df)/(ds)(\partial s)/(\partial x) +(df)/(dw) (\partial w)/(\partial x)

because we have
(\partial s)/(\partial x) =1 and
(\partial w)/(\partial x) =1

then
(\partial u)/(\partial x) =f'(s)+f'(w)


(\partial^(2) u )/(\partial x^(2) ) =(\partial)/(\partial x) (f'(s))+ (\partial)/(\partial x) (f'(w))


(\partial^(2) u )/( \partial x^(2) ) =(d)/(ds) (f'(s))(\partial s)/(\partial x) +(d)/(ds) (f'(w))(\partial w)/(\partial x)


(\partial^(2) u )/( \partial x^(2) ) =f''(s)+f''(w)

Regarding the derivatives with respect to time


(\partial u)/(\partial t)=(df)/(ds) (\partial s)/(\partial t)+(df)/(dw) (\partial w)/(\partial t)=-(df)/(ds) =-f'(s)

then
(\partial^(2) u )/(\partial t^(2) ) =(\partial)/(\partial t) (-f'(s))=-(d)/(ds) (f'(s))(\partial s)/(\partial t) =f''(s)

we see that
(\partial^(2) u )/( \partial x^(2) ) =f''(s)+f''(w) \\eq f''(s)=(\partial^(2) u )/(\partial t^(2) )


u(x,t)=f(x-t)+f(x+1) doesn´t satisfy the wave equation.

User Ndarriulat
by
5.1k points